1997
DOI: 10.1002/clc.4960200713
|View full text |Cite
|
Sign up to set email alerts
|

Vasospastic angina induced by nonsteroidal anti‐inflammatory drugs

Abstract: Summary:We report two cases of vasospastic angina associated with anaphylactic reaction caused by nonsteroidal antiinflammatory drugs (NSAIDs). Both patients exhibited anaphylactic manifestations, such as general rash and urticaria, along with angina pectoris with electrocardiographic ST-segment elevations after suppository administration of diclofenac sodium or indomethacin, the most commonly used NSAIDs. Although these patients had normal coronary arteriograms, intracoronary administration of ergonovine or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…Several reports have shown that type I variant of Kounis syndrome has better prognosis than type II variant [108]. However, in both types the prognosis depends on the magnitude of the initial allergic response, the patient's sensitivity, the patient's comorbidity, the site of antibodyantigen reaction, the allergen concentration and the route of allergen entrance.…”
Section: Clinical Relevancementioning
confidence: 96%
“…Several reports have shown that type I variant of Kounis syndrome has better prognosis than type II variant [108]. However, in both types the prognosis depends on the magnitude of the initial allergic response, the patient's sensitivity, the patient's comorbidity, the site of antibodyantigen reaction, the allergen concentration and the route of allergen entrance.…”
Section: Clinical Relevancementioning
confidence: 96%
“…Individuals with atopy are at increased risk of developing Kounis syndrome compared to normal individuals, and often experience worse symptoms due to an amplified inflammatory response (10,11). Prognosis depends on several elements, including magnitude of the initial response, patient sensitivity, comorbidity, site of antibody-antigen reaction, allergen concentration, and the route of allergen entrance (12). Although adults are more frequently affected, events in children have also been documented (13,14).…”
Section: Discussionmentioning
confidence: 97%
“…Proposed mechanisms include mechanical irritation triggering a myogenic reflex [6,7], stress receptor activation [8], and platelet aggregation at the catheter tip with release of vasoactive agents [9]. Several underlying etiologies have been documented including hypercholesterolemia, ergot toxicity, exercise, L-thyroxin therapy, hyperosmolar contrast medium, nonsteroidal anti-inflammatory drugs, cigarette smoking, and alcohol [7,8,[10][11][12][13][14][15][16][17][18]. In accordance with the presence of mild coronary artery disease (CAD) in the LAD and LCx in this patient, she also fits the typical prototype of patients predisposed to coronary vasospasm as previously defined by provocative testing with ergonovine [19].…”
Section: Discussionmentioning
confidence: 98%